The topsy turvy world of quantum computing. - Mullins, J. (IEEE spectrum)
The weirdest parts of physics are now the cutting edge of computing technology. Quantum computers are no longer seen as weird curiosities but as the powerful future of the computer industry, and the debate is shifting from whether they will ever become a reality to when they will do so. The excitement is not due to their power, although they undoubtedly will be more powerful than today's models. Their big selling point is that they can solve problems and carry out simulations that are basically impossible on conventional computers. One of the strongest forces driving the development of quantum computers is the fear that they will crack with ease secret codes that are impervious to other computers. This paper describes the principles of quantum computing including quantum information, algorithms, entanglement and error correction